A Transitivity Analysis on Epic Rap Battle of Presidency Song - Diah Supatmiwati; Billy Sukma Dwiprasetyo; Puspita Dewi (LPPM Universitas Bumigora Mataram, 2022)
The aim of this research is to analyze the Transitivity System of Epic Rap Battle of Presidency, a song by SkinnyIndonesian24, which was popular in 2019. To reveal the constituents of Transitivity System, it was considered to use theory by M.A.K. Halliday about Systemic Functional Linguistics in the branch of Ideational Metafunction, and the data were analyzed by using composite qualitative descriptive method where numbers and percentage were also involved. This research shows that the song is dominated by Material Process type for about 37 occurrences (40.2%) and it is followed by 33 Relational (35.9%), 12 Mental (13.0%), 7 Behavioral (7.6%), 2 Verbal (2.2%), and 1 Existential Process (1.1%). The dominance of Material Process indicates that the Epic Rap Battle of Presidency song is on the state of Material Process where the song is mainly talk about action and event. Keywords:Transitivity, Material Process, Systemic Functional Linguistics